Investigation of the dynamics of lipid peroxidation products in the blood and liver of rats of different ages with experimentally induced dyslipoproteinemia on the background of mechanical damage - O. N. Pavlova; O. N. Tulaeva; O. N. Gulenko; D. S. Gromova; V. V. Leonov; E. V. Lukenyuk (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье)
From the modern point of view, dyslipoproteinemia and its clinical manifestation – atherosclerosis – is a complex multifactorial process, which is based on inflammation, and, as a consequence, oxidative stress.The aim of the study was to identify the dynamics of the concentration of diene conjugates and malondialdehyde in the blood and liver of rats of different ages under oxidative stress caused by modeling dyslipoproteinemia with subsequent mechanical injury of skeletal muscle.Materials and methods. The study was carried out on white mongrel healthy male rats 24 months old (120 individuals) and 6 months old (120 adults). All old and young animals were divided into four subgroups within their group, 30 animals each. The animals of the first subgroup in the groups of old and young rats are intact rats. Animals of the second subgroup in each group had a mechanical dissection in the area of the middle third of the calf muscle of the hind limb. Animals of the third and fourth subgroups of each group were subjected to dyslipoproteemia modeling. After the specified time, the animals of the fourth subgroup of both groups were injured in the middle third of the calf muscle of the hind limb.Conclusions. Mechanical injury of the calf muscle in combination with dyslipoproteemia is characterized by intense oxidative stress and leads to an increase in the concentration of malondialdehyde and diene conjugates in the liver and blood tissues of rats, and in old animals these processes are more pronounced than in young ones.